Chinese communist politics in action. Ed. by A. Doak Barnett. Contributors: R. Hofheinz, Jr., R.H. Solomon, I.J. Kim [a.o.] (University of Washington Press, 1969)
With graphs, ills, index, maps and tabs. Washington paperbacks on Russia and Asia. WPRA-7.